Consequences of 1.5 °C and 2 °C global warming levels for temperature and precipitation changes over Central Africa. (9th May 2018) - Mba, Wilfried Pokam; Longandjo, Georges-Noel T; Moufouma-Okia, Wilfran; Bell, Jean-Pierre; James, Rachel; Vondou, Derbetini A; Haensler, Andreas; Fotso-Nguemo, Thierry C; Guenang, Guy Merlin; Tchotchou, Angennes Lucie Djiotang; Kamsu-Tamo, Pierre H; Takong, Ridick R; et al.
Abstract: Discriminating climate impacts between 1.5 °C and 2 °C warming levels is particularly important for Central Africa, a vulnerable region where multiple biophysical, political, and socioeconomic stresses interact to constrain the region's adaptive capacity. This study uses an ensemble of 25 transient Regional Climate Model (RCM) simulations from the CORDEX initiative, forced with the Representative Concentration Pathway (RCP) 8.5, to investigate the potential temperature and precipitation changes in Central Africa corresponding to 1.5 °C and 2 °C global warming levels. Global climate model simulations from the Coupled Model Intercomparison Project phase 5 (CMIP5) are used to drive the RCMs and determine timing of the targeted global warming levels. The regional warming differs over Central Africa between 1.5 °C and 2 °C global warming levels. Whilst there are large uncertainties associated with projections at 1.5 °C and 2 °C, the 0.5 °C increase in global temperature is associated with larger regional warming response. Compared to changes in temperature, changes in precipitation are more heterogeneous and climate model simulations indicate a lack of consensus across the region, though there is a tendency towards decreasing seasonal precipitation in March–May, and a reduction of consecutive wet days. As a drought indicator, a significant increase in consecutive dry days was found. Consistent changes of maximum 5 day rainfall are also detected between 1.5 °C vs. 2 °C global warming levels.